2005
DOI: 10.4049/jimmunol.175.12.7855
|View full text |Cite
|
Sign up to set email alerts
|

Targeting LFA-1 and CD154 Suppresses the In Vivo Activation and Development of Cytolytic (CD4-Independent) CD8+ T Cells

Abstract: Short-term immunotherapy targeting both LFA-1 and CD40/CD154 costimulation produces synergistic effects such that long-term allograft survival is achieved in the majority of recipients. This immunotherapeutic strategy has been reported to induce the development of CD4+ regulatory T cells. In the current study, the mechanisms by which this immunotherapeutic strategy prevents CD8+ T cell-dependent hepatocyte rejection in CD4 knockout mice were examined. Combined blockade of LFA-1 and CD40/CD154 costimulation did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 65 publications
2
36
1
Order By: Relevance
“…1b). These studies expand upon our previous observations that CD8 ϩ GICs in hepatocyte rejectors express a CTL phenotype (CD8 ϩ CD43 ϩ ) (47) and that the detection of in vivo allocytotoxicity correlates with graft survival status (46,47).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…1b). These studies expand upon our previous observations that CD8 ϩ GICs in hepatocyte rejectors express a CTL phenotype (CD8 ϩ CD43 ϩ ) (47) and that the detection of in vivo allocytotoxicity correlates with graft survival status (46,47).…”
Section: Discussionsupporting
confidence: 64%
“…One study of cardiac allografts reported that host CD4 ϩ T cells are necessary to license dendritic cells for CD8 ϩ T cell activation, CTL function, and CD4-dependent graft rejection (45). However, the development of CTL effectors under CD4-independent conditions in response to allograft tissues such as skin, intestine, and hepatocytes has not been investigated, except for reports by our group showing that the rejection of allogeneic liver parenchymal cells in the absence of CD4 ϩ T cells is accompanied by in vivo cytotoxic effector function (46,47).…”
Section: A Ctivation and Maturation Of Cd8mentioning
confidence: 70%
See 3 more Smart Citations